Peningkatan Hasil Belajar Menggunakan Model Cooperatif Learning Tipe Teams Assisted Individualization pada Mata Pelajaran Bahasa Indonesia di Kelas III SDN 13 Surau Gadang - Yetti, Puji Mustika; Azima, Nana Fauzana (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to describe the improvement of student learning outcomes through the implementation of the Teams Assisted Individualization type of Cooperative Learning model in Indonesian language learning in class III SDN 13 Surau Gadang. This research is a Classroom Action Research (CAR) with qualitative and quantitative approaches, conducted in two cycles. Each cycle consists of the stages of planning, implementation, observation, and reflection. The subjects of the research are the teacher and 28 students in class III. The results of the research indicate an improvement in all aspects. The average assessment of the teaching module improved from 89.58% (Good category) in cycle I to 95.83% (Very Good) in cycle II. The aspect of teachers improved from 80% to 92.5%, and the aspect of students from 78.75% to 90%, both in the Very Good category. The learning outcomes also showed improvement, both in knowledge aspects (from 71.08% to 87.86%) and skills (from 70.41% to 85.32%). Thus, the use of the Teams Assisted Individualization model has proven to improve the learning outcomes of Indonesian language for third-grade elementary school students.